2016
DOI: 10.1142/s0129065716500131
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition with Eigen Features of Frequency Band Activities Embedded in Induced Brain Oscillations Mediated by Affective Pictures

Abstract: In this study, singular spectrum analysis (SSA) has been used for the first time in order to extract emotional features from well-defined electroencephalography (EEG) frequency band activities (BAs) so-called delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-16 Hz), beta (16-32 Hz), gamma (32-64 Hz). These five BAs were estimated by applying sixth-level multi-resolution wavelet decomposition (MRWD) with Daubechies wavelets (db-8) to single channel nonaveraged emotional EEG oscillations of 6 s for each scalp location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Moreover, finding key emotional states to be recognized is mandatory; for example, six emotions were detected in [42,45,106,120,122,192], whereas in [108], a real-time EEG signal to classify happy and unhappy emotions was proposed, and in [113], a fear evaluation system was proposed. In our review, we found that most of the articles aim to detect unpleasant, pleasant, and neutral emotions, such as in [105,217], or positive, negative, and neutral emotions that are based on the valence-arousal dimensional emotion model, as in [159,206].…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, finding key emotional states to be recognized is mandatory; for example, six emotions were detected in [42,45,106,120,122,192], whereas in [108], a real-time EEG signal to classify happy and unhappy emotions was proposed, and in [113], a fear evaluation system was proposed. In our review, we found that most of the articles aim to detect unpleasant, pleasant, and neutral emotions, such as in [105,217], or positive, negative, and neutral emotions that are based on the valence-arousal dimensional emotion model, as in [159,206].…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
“…These proposed systems aim to explore or improve EEG-based emotion recognition systems. [2,39,41,42,49,50,57,61,63,92,104,108,109,117,131,136,149,152,157,173,174,185,186,189,191,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209]217,219,[223][224][225]229,[262][263][264][265][266]<...>…”
Section: Monitoringmentioning
confidence: 99%
“…This methodology is general and could be used in any situation where multiple neurons are recorded, whether there be a single type of trial or multiple trial types, as considered here. For example, this application could be used in the study of motor commands for gaze control (Takemura et al, 2001), neuronal oscillators (Schwemmer and Lewis, 2011; Geertsema et al, 2015; Aydin et al, 2016) or other brain studies such as deep brain stimulation (Florin et al, 2013). Further, it could be used for research in brain-computer interfaces (Carmena et al, 2003;Ortiz-Rosario and Adeli, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and the FOV θ is In our eCley system, the pixel pitch is 3.2µm; the channel image has a size of 55 × 55 pixels; and the focal length f is 778µm. According to (2) and 3, the angular resolution ∆θ =0.235 • and the FOV θ =6.345 • are obtained.…”
Section: Spatial Coordinate Calculationmentioning
confidence: 99%
“…Some recently proposed examples include inspiration by music [41,40], physics [43,42,44], swarm behavior [34,37,36]. Artificial Intelligence is often integrated within robot controllers [45,28] and combined to neural systems for Machine Intelligence [19,2,13].…”
Section: Introductionmentioning
confidence: 99%